PERAN MEDIA SOSIAL TIKTOK DALAM MEMBANGUN KESADARAN ANTI-BULLYING (ANALISIS KASUS: TIMOTHY ANUGERAH SAPUTRA) - Tonna Balya; Putri Amara (SYMBOLE, 2025)
Digital media plays a crucial role in shaping Sosial awareness regarding the issue of bullying, which increasingly occurs within virtual spaces. This critical descriptive qualitative study analyzes the role of the Sosial media platform TikTok in building anti-bullying awareness through the case study of the activism and subsequent death of Timothy Anugerah Saputra, a student at FISIP Udayana University, Bali. The findings indicate that while TikTok serves as an effective advocacy platform for spreading empathy through storytelling, its virality features (Duet/Stitch) ironically accelerated systematic and fatal cyberbullying. The case highlights a failure of the dual system, encompassing inadequate platform moderation and insufficient institutional support, which failed to adequately respond to the massive attacks. This emphasizes the critical need for ethical digital media utilization and the strengthening of psychoSosial interventions in the online sphere